Entre éthique dharmique et pratiques agraires productivistes, usage des pesticides chez les Bishnoï du Rajasthan - Maria Mélanie Chauveau (VertigO)
The Bishnoi are members of a religious community founded in the 15th century in the Thar Desert of Rajasthan. Originally based on 29 precepts, many of which codify relationships with other living beings, animals and plants, their religious doctrine, Bishnoism, prescribes an ethic of life in which compassion for all living beings (jīv) and avoidance of harm to them are paramount principles. Mostly farmers, the Bishnoi are nowadays facing profound transformations brought about by modernity and the intensification of their agriculture (extension of irrigation systems, use of machinery, fertilizers and pesticides).Based on an ethnographic study, this article examines the ethical and religious dilemmas generated by the use of pesticides that destroy living organisms. It documents undergoing arrangements to reconcile emerging practices in contradiction with founding principles.